Inheritance patterns and genome-wide association study of tropical early-maturing maize inbred lines under striga infestation and drought stress environments - Adewale, Samuel A. (Obafemi Awolowo University, 2021)
This study determined the gene action controlling grain yield and other agronomic traits among newly-developed early-maturing maize inbred lines under drought stress, Striga infestation, optimal conditions and across research environments; examined the combining ability of the early maize inbred lines under each and across research environments; classified the inbred lines into heterotic groups using DArTseq (Diversity Arrays Technology sequencing) markers and combining ability effects methods and determined genome-wide marker-trait association of key Striga resistance agronomic traits using representative DArTseq markers. These were with a view to facilitating efficient maize hybrid development programme for stress and non-stress environments in sub-Saharan Africa. The research was carried out in two phases which included: (1) generation and evaluation of testcrosses, and (2) genome-wide association study. In the first phase, five inbred testers were crossed to thirty-eight inbreds using line x tester mating design. A total of 190 testcross hybrids plus ten hybrid checks (the hybrid trial) were evaluated under artificial Striga infestation, drought stress and optimal environments from 2017 to 2019. In the second phase, 132 inbred lines including one check (the inbred trial) were evaluated under artificial Striga infestation and optimal conditions from 2017 to 2019. The 132 inbred lines were genotyped using DArTseq markers for the molecular analysis. Data collected on grain yield and other measured traits were subjected to Analysis of Variance (ANOVA). The testcrosses were further subjected to line x tester analysis. Results revealed preponderance of GCA over SCA sum of squares for grain yield and most other assayed traits under Striga-infested, optimal and across research conditions whereas under drought stress conditions, there was predominance of SCA effects over GCA effects for grain yield and most other traits. Inbred lines TZEI 1203 and TZEI 1348 were identified as having highest GCA effects across all research conditions. The inbreds were classified into two, three and four heterotic groups each by the DArTseq-SNP molecular marker-based GD, HGCAMT and HSGCA methods, respectively. The DArTseq grouping method was the most efficient in classifying the inbreds into heterotic groups, followed by the HGCAMT method and then HSGCA method. The 132 inbred lines were classified into two major clusters by both the population structure and neighbour joining phylogenetic analyses. Twenty-four markers located on several maize chromosomes were found to be significantly associated with Striga adaptive traits under Striga infestation. Three putative genes GRMZM2G060216, GRMZM2G057243 and GRMZM2G164743 associated with plant defense mechanism under Striga infestation were detected on chromosomes 3, 9 and 10, respectively. The study concluded that additive gene effects were predominant in controlling the inheritance of grain yield and other traits under Striga-infestation while under drought stress, non-additive gene effects were more important.